2005
DOI: 10.1182/blood-2005-03-1291
|View full text |Cite
|
Sign up to set email alerts
|

CD34 expression by mast cells: of mice and men

Abstract: calcium by sodium citrate used as an anticoagulant with blood collection. However, protein-S dimerization occurs at concentrations far above the plasma concentration: "at 17 M, the associated product is principally a dimer." 2 Inspection of Figure 5 of the paper by Pauls et al 2 indicates that, at the free protein-S concentration present in plasma (ϳ 150 nM), protein S is principally a monomer.In spite of this, Dr Mann believes that inhibitory protein-S dimers are present at the start of our experiments, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…MC requirement was confirmed by using mice reconstituted with c-kit-defective BM (KitW-sh/KitW-sh) (40,41). Although human CD34 antigen expression ceases as MCp differentiate into mature MC in the peripheral tissues, migrating MCp express the antigen and, thus, should still be valid targets for therapy (7). Additionally, because deletion of the CD34-encoding gene has no obvious effects on murine development or steady-state immune responses, strategies to target this antigen in human MC are likely to be well tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MC requirement was confirmed by using mice reconstituted with c-kit-defective BM (KitW-sh/KitW-sh) (40,41). Although human CD34 antigen expression ceases as MCp differentiate into mature MC in the peripheral tissues, migrating MCp express the antigen and, thus, should still be valid targets for therapy (7). Additionally, because deletion of the CD34-encoding gene has no obvious effects on murine development or steady-state immune responses, strategies to target this antigen in human MC are likely to be well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is further strengthened by reports that, in human, iMC lack CD34 (6), because we previously have shown that, although the human Cd34 gene is expressed in trafficking MCp, it is shut off as they differentiate into mature MC in the periphery (reviewed in ref. 7). Our revelation that the iMC are MC should greatly enhance the development of additional interventional therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD34 is lost during mast cell maturation. 41 Therefore, the mast cell progenitors identified in the present study are likely more immature than CD34 2 CD117 1 blood cells with mast cell-forming capacity quantified in mastocytosis patients. 42 To summarize, we have identified a rare population of human mast cell progenitors in blood, which gives rise to predominantly mast cells, although the limited cell division capacity and partial loss of FceRI after culture in vitro prevent us from concluding their full commitment to the mast cell lineage.…”
mentioning
confidence: 99%
“…17 CD34 is a cell-surface sialomucin originally identified as a marker of hematopoietic stem cells (HSCs), early hematopoietic progenitors, and vascular endothelia 18 and was more recently identified on mast cells and eosinophils. 19,20 In fact, it was shown that in a mouse model of asthma, 50% of the recruited eosinophils were CD34 ϩ . 20 Surprisingly, despite the wide attention CD34 has garnered as a marker of hematopoietic precursors (Ͼ 14 000 citations), little is know of its function on these cells.…”
Section: Introductionmentioning
confidence: 99%